A full color visual educating tool to improve renal diet compliance - Cecile Verseput (The Korean Society of Nephrology, 2012)
The objective is to simplify Renal diet education of a newly diagnosed, illiterate/non-English speaking CKD patient by using a 5 step concept that is explained by a fully illustrated color manual. The 5 steps to be followed are as follows: Step 1. What foods are eaten daily? The renal dietitian is faced with many challenges when taking a diet history & educating a newly diagnosed CKD patient. It is of utmost importance to tailor education to specific patient's needs & to adapt the diet prescription to the patient's literacy level, culture, socio-economic circumstances & eating habits. Step 2. How kidneys work. The damaged kidney is portrayed as a sieve with very fine mesh that does not allow normal kidney functions. Once the patient understands that his uremic symptoms are related to diet & damaged kidneys, he is willing to change his old eating habits. RRT is explained visually. Step 3. What to eat. The calculated, technical diet prescription is explained in an understandable way by a visual tool called "The renal plate" that was specifically developed. The Renal plate is based on adjusting the Basic 3 Food Groups by making use of the South African Renal exchange lists. Step 4. What not to eat. Foods to avoid due to high sodium, phosphate & potassium are presented by illustrations. Step 5. How much to eat. Portion sizes are addressed through visuals since "The renal plate" only focuses on types of foods in a specific food group, not on quantity of each food group to be eaten. Compliance to a renal diet is an integral part of patient care. If understandable renal diet education is linked to uremic symptoms & starts as soon as the patient is diagnosed, there is far better future diet compliance & disease outcome.